Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1101/319103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Error-correcting dynamics in visual working memory

Abstract: Working memory is critical to cognition, decoupling behavior from the immediate world. Yet, it is imperfect; internal noise introduces errors into memory representations (1, 2). Such errors accumulate over time (3)(4)(5) and increase with the number of items simultaneously held in working memory (6-10). Here, we show that error-correcting attractor dynamics mitigate the impact of noise on working memory. These dynamics pull memories towards a few stable representations in mnemonic space, inducing a bias in mem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(79 citation statements)
references
References 35 publications
(38 reference statements)
15
64
0
Order By: Relevance
“…; or simply as a natural result of the fact that noise in memory is relatively independent for each item (Fougnie et al, 2012;Schurgin et al 2020;Panichello, DePasquale, Pillow, & Buschman, 2018;Wilken & Ma, 2004). Thus, variation between multiple working memory items appears to be an unavoidable and natural byproduct of working memory maintenance and so it is important to consider what this means for memory driven attentional guidance.…”
Section: )mentioning
confidence: 99%
“…; or simply as a natural result of the fact that noise in memory is relatively independent for each item (Fougnie et al, 2012;Schurgin et al 2020;Panichello, DePasquale, Pillow, & Buschman, 2018;Wilken & Ma, 2004). Thus, variation between multiple working memory items appears to be an unavoidable and natural byproduct of working memory maintenance and so it is important to consider what this means for memory driven attentional guidance.…”
Section: )mentioning
confidence: 99%
“…The build-up of serial dependencies during an experimental session has further implications for how we interpret their functional role. If serial dependence was an adaptation to exploit the world's tendency to remain stable 23 , and this adaptation could occur in the time scale of hour fractions (as recently shown for systematic biases in delayed-estimation of color tasks 27 ), memorizing a sequence of uncorrelated stimuli should decrease serial dependence in the course of an experimental session. Alternatively, if hard-wired mechanisms underlie serial dependence, we wouldn't expect any change.…”
Section: Discussionmentioning
confidence: 87%
“…The reasoning is that because similar stimuli usually elicit similar behavior, the brain would incorporate mechanisms to exploit these patterns 23 . Along these lines, a recent study has shown that systematic biases in color working memory change in the course of an experimental session to adapt to stimulus statistics 27 , arguing that systematic biases seen in delayed-estimation of color reflect real-world statistics. If similar adaptive plasticity operated for serial dependence in the time scale of the experimental session, we would expect to see a reduction of serial biases as one is exposed to a sequence of uncorrelated stimuli.…”
Section: Color Serial Dependence Builds Up In the Course Of An Experimentioning
confidence: 99%
See 2 more Smart Citations